The Influence of the Development of Emotional Skills in the Performance of Special Operations Troops in Stressful Situations (Global Journal of Human-Social Science, 2024)
This study focuses on the influence of emotional skills development on the performance of special operations forces specifically within the context of the Special Forces Course in Brazil The research aims to fill a knowledge gap by exploring how enhancing these skills can positively impact coping with stressful situations in high-risk operational environments The central problem involves understanding how modifying military training methods can assist fighters in dealing with stressful situations The hypothesis suggests that improving the psychosocial aspect of military training can result in significant benefits The study adopts a mixed-methods approach combining numerical data and analysis of open-ended responses It employs an experimental design with characteristics of action research implementing planned interventions to analyze the results The research is longitudinal with data collection at the beginning and throughout the Special Forces Course involving 30 students stratified from the Commando Actions Course Results are analyzed in four main areas personal planning mindfulness emotional intelligence and interpersonal relationships Personal planning shows an overall improvement of 3 4 emphasizing precise decision-making problem prevention and time optimization Mindfulness exhibits the highest perceived increase at 12 2 highlighting practices that reduce stress and maladaptive thoughts Emotional intelligence records a 9 8 increase indicating the development of individual and social characteristics Interpersonal relationships demonstrate a 6 8 increase with improvements in information reception and patience The Questionnaire on Developed Practices reveals valuable insights Meditative practices mentioned 24 times stand out with an emphasis on visualization and breath control
Keywords: emotional skills; military performance; meditative practices; special forces course